Method 1
Divide both sides by 7 first to get
14 = 7(2x-4)
14/7 = 7(2x-4)/7
2 = 2x-4
Then add 4 to both sides
2+4 = 2x-4+4
6 = 2x
2x = 6
Finally, divide both sides by 2
2x/2 = 6/2
x = 3
which is the final answer
------------------------------------------------------------------------------------------------
Method 2
Distribute the 7 through to each term in the parenthesis
14 = 7(2x-4)
14 = 7*2x + 7*(-4)
14 = 14x - 28
Then we follow similar steps as done earlier. Add 28 to both sides
14+28 = 14x-28+28
42 = 14x
14x = 42
Then divide both sides by 14 to fully isolate x
14x/14 = 42/14
x = 3
Either way we get the same result. As to which method you pick (if you could only choose one), its up to you based on whichever you find easier.
The basic idea with either method is that we follow PEMDAS in reverse to undo everything happening to x. This way we fully isolate it.
----------------
Checking the answer:
Plug x = 3 into the original equation. Simplify to get
14 = 7(2x-4)
14 = 7(2*3-4)
14 = 7(6-4)
14 = 7*2
14 = 14
This confirms the answer. As you can see, if we know the value of x, we use PEMDAS to simplify both sides. But if we don't know x, and want to find it, then we follow PEMDAS in reverse.